Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.5507/bp.2012.090
|View full text |Cite
|
Sign up to set email alerts
|

Detection of diketopiperazine and pyrrolnitrin, compounds with anti-Pythium insidiosum activity, in a Pseudomonas stutzeri environmental strain

Abstract: Aims. Screening of bacterial flora for strains producing metabolites with inhibitory effects on the human pathogenic oomycete Pythium insidiosum. Separation and characterization of extracts from Pseudomonas stutzeri with anti-Pythium inhibitory activity. Search for genes with anti-Pythium effect within the genome of P. stutzeri. Methods. A total of 88 bacterial strains were isolated from water resources in northeastern Thailand. Two screening methods were used to establish their inhibitory effects on P. insidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…It is well known that the therapy of pythiosis has posed a challenge in recent decades as the current treatment options are highly variable and often lead to failure 14 . Therefore, many studies have searched for antimicrobial agents, natural compounds or secondary metabolites from microorganisms against P. insidiosum and results of in vitro testing are quite promising 6,7,[15][16][17][18][19][20][21] . The present study evaluated antimicrobial effects against P. insidiosum of xanthyletin and two fractions of the crude extracts from P. stutzeri ST1302 and K. pneumoniae ST2501.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that the therapy of pythiosis has posed a challenge in recent decades as the current treatment options are highly variable and often lead to failure 14 . Therefore, many studies have searched for antimicrobial agents, natural compounds or secondary metabolites from microorganisms against P. insidiosum and results of in vitro testing are quite promising 6,7,[15][16][17][18][19][20][21] . The present study evaluated antimicrobial effects against P. insidiosum of xanthyletin and two fractions of the crude extracts from P. stutzeri ST1302 and K. pneumoniae ST2501.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the treatment of pythiosis is still challenging. Previous studies demonstrated that natural compounds from plants and secondary metabolites from microorganisms had relatively good in vitro antimicrobial activity against P. insidiosum 6,7 . Xanthyletin, a natural compound of green plants, is classified in a group of pyranocoumarins, coumarin derivatives.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One such example includes the isolation of chemical entities from other P. stutzeri species that have yielded compounds such as alkyl-substituted diketopiperazines, pyrazines, and siderophores (Figure 4; Bañeras et al, 2013;Zawadzka et al, 2006). The diketoperazine that was isolated from the P. stutzeri strain ST1302 was shown to be active against the pathogenic fungus-like Pythium insidiosum using the disk diffusion method (Thongsri et al, 2014). The P. stutzeri strain (40M1) which was active in our bioassay against both the Gram-positive S. aureus and B. subtilis (Table 3) The different sample collection sites revealed minor variation in their microbial diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Many DKPs were considered as fermentation artifacts earlier, but now their antifungal, anti-mitotic and antibacterial roles have been unveiled. P. stutzeri showed the production of several DKPs with antiPythium insidiosum activity which is a mammalian pathogen (Thongsri et al 2014). DKPs mixture containing cyclo-lPro-Met, cyclo-l-Pro-l-Phe and cyclo-l-Pro-Val ( Fig.…”
Section: Advances In Identification and Characterization Of Secondarymentioning
confidence: 99%